Impact of β-blockers on survival outcomes in patients with unresectable hepatocellular carcinoma - Ellery Altshuler; Mahmoud Aryan; Govind Kallumkal; Hanzhi Gao; Jake Wilson; Ahmed Ouni; Edward De Leo; Wissam Hanayneh; Kelsey Pan (Hepatic Oncology, 2022)
Background: β-blockers (BBs) have shown promise in improving overall survival (OS) in patients with breast, ovarian, pancreatic and lung cancer. However, few studies have evaluated the impact of BBs on unresectable hepatocellular carcinoma (HCC). Methods: The authors compared clinical data and outcomes between unresectable HCC patients based on whether they were prescribed BBs. Results: There was significantly decreased disease progression in the BB group compared with the non-BB group (22.8 vs 28.0%; p < 0.05). No difference was seen in OS or progression-free survival between groups. Those specifically on selective BBs had improved OS (hazard ratio: 0.75; 95% CI: 0.61–0.94; p = 0.01) and progression-free survival (hazard ratio: 0.66; 95% CI: 0.45–0.96; p = 0.03) compared with non-BB patients. Conclusion: Although the authors' study did not demonstrate that BBs improve OS in HCC, it did show decreased disease progression among patients with HCC who were taking BBs compared with those who were not.